Menguji Kepemimpinan Demokratis Kepala Sekolah di SMA Pancasila 3 Paranggupito dalam Memimpin Guru - Pingkan Elora Priyaningsih; Zaki Afifi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The principal's democratic leadership plays a significant role in encouraging teacher participation and creating open, two-way communication in school management. This study aims to examine and describe the principal's democratic leadership practices in leading teachers at Pancasila 3 Paranggupito High School, specifically in the learning evaluation program. The method used in this study was a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation studies. Data were then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the principal implements democratic leadership through four interrelated learning evaluation programs: academic supervision, student learning outcome evaluation, learning process evaluation, and teacher evaluation and reflection meetings. These four programs demonstrate active teacher involvement in decision-making, open, two-way communication, and deliberative decision-making. The conclusion of this study is that the principal's democratic leadership is able to create a participatory work climate and support the continuous improvement of learning quality in the school.